The impact of government expenditure on pro poor sectors in reducing poverty: A case of Kibaha District - Musiba, Crispin (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirement for the award of Master’s of Science in Economics (Msc. Eco) of Mzumbe University.